Influence of Multi-Scale Meteorological Processes on PM2.5 Pollution in Wuhan, Central China - Miao, Yucong; Zhang, Xinxuan; Che, Huizheng; Liu, Shuhua (Frontiers in Environmental Science, 2022)
Heavy particulate matter with an aerodynamic diameter less than 2.5 μm (PM2.5) pollution frequently happens in Wuhan under unfavorable meteorological conditions. To comprehensively understand the complex impact of both regional-scale synoptic forcing and local-scale processes within the planetary boundary layer (PBL) on air quality in Wuhan, this study analyzed long-term PM2.5 concentration measurement, near-surface and upper-air meteorological observations from March 2015 to February 2019, in combination with the Modern-Era Retrospective Analysis for Research and Applications version 2 (MERRA-2). We found that in winter the day-to-day change of PM2.5 pollution level in Wuhan was governed by the synoptic warm/cold advection, in addition to the high emissions of pollutants. The synoptic condition can largely determine both the vertical development of PBL and horizontal transport of pollutants. When a high-pressure system is located to the north of Wuhan at the 900-hPa level, the induced warm advection above 1000 m can enhance the thermal stability of lower troposphere and inhibit the development of daytime PBL, leading to a decreased dispersion volume for pollutants. Meanwhile, within the PBL the pollutants emitted from Henan, Shandong, and Anhui provinces can be transported to Wuhan, further worsening the pollution. Our results highlight the importance of coordinated pollution controls in Central China and adjacent north regions under the unfavorable synoptic condition.